La semantica cognitiva di Kant e l’ornitorinco tra topi, uova e zanzare: possibilità di tenuta di uno schematismo enciclopedico / / Kant and the Platypus cognitive semantics between mice, eggs and mosquitoes: Is an encyclopaedic schematism tenable? - Bianchi, Edoardo Maria (Rivista Italiana di Filosofia del Linguaggio)
Kant and the Platypus, which represented a real turn in Umberto Eco’s thinking, is above all, as its introduction states, a work of cognitive semantics. We will focus then on a chapter, the third one, which is precisely devoted to the elaboration of this semantic proposal, defined by Eco himself as a «possible neo-schematism» (ECO 1997: 104). Given a semiotic model that wants to keep together the structuralist tradition and the interpretive one, we consider in fact the maintaining of a cognitivist and schematizing perspective highly problematic. We will analyse then the notion of cognitive type – which revises in a non trascendental sense the Kantian schema – and the correlated ones of nuclear and molar content: in this way, we will see that, notwithstanding an absolute hierarchic primacy ascribed to the perceptual level that presides at the acts of recognition and reference, the stress on the role of encyclopaedic competence smashes the notion of scheme, which is now defined in terms of regularities rather than in terms of rules.